Host-driven evolution of PCV2: insights into genetic diversity and adaptation - Franzo, Giovanni; Legnardi, Matteo; Poletto, Francesca; Baston, Riccardo; Cecchinato, Mattia; Drigo, Michele; Tucciarone, Claudia Maria (Frontiers in Immunology, 2025)
IntroductionsPorcine circovirus type 2 (PCV2) is a significant pathogen in swine, exhibiting notable genetic and phenotypic diversity. This study explores the evolutionary mechanisms influencing PCV2 variability, emphasizing the role of viral features and host environment.MethodsAn extensive collection of globally available ORF2 sequences of the main PCV2 genotypes (i.e., PCV2a, PCV2b, and PCV2d) sampled from wild boars and domestic pigs was analyzed, using a combination of phylodynamic approaches and biostatistical methods to infer the presence and patterns of selective pressures in different virus population subsets.ResultsSignificant differences were observed between strains collected from domestic and wild populations, with the former appearing to be under stronger selective pressures at specific capsid positions. These pressures are likely driven by immune-mediated selection acting on critical residues for immune system recognition and evasion. A comprehensive evaluation of substitution patterns also revealed a trend toward maintaining or enhancing amino acid polarity, with neutral residues often replaced by polar or charged ones. This shift may influence the virus interaction with host proteins, particularly glycosaminoglycans such as heparan sulfate-like molecules. The observed variability among hosts and genotypes highlights both the importance of host environment as a key driver of viral evolution and the plasticity of PCV2 adaptability, with multiple alternative evolutionary pathways seemingly being selected.DiscussionThe findings underscore the complex evolutionary trajectories followed by PCV2 on a global scale and suggest that the intensification of pig farming and associated management practices may have significantly shaped PCV2 evolution, contributing to the current epidemiological landscape.